Penerapan Model Problem Based Learning Dalam Meningkatkan Pemahaman pada Mata Pelajaran Fikih Siswa Kelas VII MTs Yaspend Muslim Pematang Tengah - Indra Syah Putra; Khadijah Khadijah (Transformasi Manageria: Journal of Islamic Education Management, 2021)
The learning model used in writing this thesis is to use a classroom action research approach. The purpose of this paper is to find out that problem based learning models can improve students' understanding of fiqh subjects for class VII students of MTs Yaspend Muslim Pematang Tengah. The conclusions that can be drawn from this paper regarding student responses after the implementation of the Problem Based Learning model in improving understanding of the subject of Jurisprudence for class VII students of MTs Yaspend Muslim Pematang Tengah are at the pre-test stage the number of students who completed as many as 10 people with a percentage of 32.25% and 21 students who did not complete, then after applying the Problem Based Learning model there was an increase in the first cycle as many as 19 students completed with a percentage of 61.29% and as many as 12 students did not complete. Because it has not met the researcher's target, it is continued in the second cycle. In the second cycle, there was an increase of 28 students who completed with a percentage of 90.32% and as many as 3 students